Genetic Mechanism of Pyrite in the Shale of the Longmaxi Formation and Its Influence on the Pore Structure: A Case Study of the Changning Area, South Sichuan Basin of SW China - He, Jiang; Yang, Lan; Shi, Xuewen; Zhao, Shengxian; Cao, Lieyan; Pan, Shulin; Wu, Feng; Wang, Meng (Frontiers in Earth Science, 2022)
Pyrite is a mineral that is commonly found in shale gas reservoirs. Its genetic mechanism and impact on pore and organic matter in shale gas reservoirs are critical for shale gas exploration. This study selects the Longmaxi shale (Lower Silurian) in the Changning area of the southern Sichuan Basin by comprehensively using a scanning electron microscope (SEM), X-ray diffraction (XRD), total organic carbon (TOC), and image processing technology. The type and characteristics of pyrite in shale reservoirs are studied, the sedimentary environment and genetic mechanism of pyrite are analyzed, and the influence of pyrite formation on organic matter enrichment and reservoir formation is evaluated. The results showed that pyrite in shale primarily forms framboidal pyrite, euhedral pyrite, and subhedral pyrite, with particle sizes ranging from 1μm to 15 μm. The maximum framboid diameter (MFD) is less than 20 μm, with the average particle size distribution of 3 μm to 5 μm. These parameters indicate the vulcanization and blocking environment. The reducing environment promotes organic matter enrichment and preservation. Framboidal pyrite has two genetic sequences: rich organic matter and poor organic matter. The development of organic matter will limit the continuous radial growth of pyrite and is conducive to the protection of pores, the formation of pyrite can reduce the activation energy of kerogen reaction and catalyze the hydrocarbon generation of organic matter, resulting in higher gas content. Framboidal pyrite content can be used to predict high-quality shale gas reservoirs.